2022
DOI: 10.4103/aja2021130
|View full text |Cite
|
Sign up to set email alerts
|

Microdeletions and vertical transmission of the Y-chromosome azoospermia factor region

Abstract: Spermatogenesis is regulated by several Y chromosome-specific genes located in a specific region of the long arm of the Y chromosome, the azoospermia factor region (AZF). AZF microdeletions are the main structural chromosomal abnormalities that cause male infertility. Assisted reproductive technology (ART) has been used to overcome natural fertilization barriers, allowing infertile couples to have children. However, these techniques increase the risk of vertical transmission of genetic defects. Despite widespr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…In particular, deletions in the AZF (azoospermia factor) region are frequently observed in men with infertility, and these genetic abnormalities can be transmitted on to offspring via ICSI. 75 , 76 , 77 , 78 , 79 Furthermore, it has been reported that AZF deletions can expand or cause new de novo deletions during the genetic transmission process via ICSI. 80 , 81 , 82 , 83 , 84 ICSI has become a widely used technique, despite the unresolved issue of potential transmission of AZF microdeletions to subsequent generations.…”
Section: Continuation Of Opinions and Discussion On Icsimentioning
confidence: 99%
“…In particular, deletions in the AZF (azoospermia factor) region are frequently observed in men with infertility, and these genetic abnormalities can be transmitted on to offspring via ICSI. 75 , 76 , 77 , 78 , 79 Furthermore, it has been reported that AZF deletions can expand or cause new de novo deletions during the genetic transmission process via ICSI. 80 , 81 , 82 , 83 , 84 ICSI has become a widely used technique, despite the unresolved issue of potential transmission of AZF microdeletions to subsequent generations.…”
Section: Continuation Of Opinions and Discussion On Icsimentioning
confidence: 99%
“…Spermatogenic failure, clinically known as oligozoospermia, cryptozoospermia, or azoospermia, can result from the AZFc microdeletion. But some patients' testicles still go through the entire spermatogenic process [18]. It is possible that patients with AZFc deletions respond effectively to AI therapy because spermatogenic tissue is still present in their testicles.…”
Section: Discussionmentioning
confidence: 99%
“…Little evidence supports a correlation between increased paternal age and the incidence of chromosome anomalies. Although some studies demonstrated an increased risk of congenital abnormalities with advanced paternal age, such as unbalanced complements, inherited reciprocal translocations, and down syndrome, the incidence of severe non-chromosomal congenital disabilities, especially those arising from new autosomal mutations, also increases with paternal age due to impaired sperm function [138]. The experience gathered from various micromanipulation methods of gametes, including zona-opening procedures, subzonal sperm insertion, and sperm microinjection into the ooplasm, have demonstrated not only their clinical utility in assisted fertilization but also suggests the potential for selective application of these techniques and their combinations in the treatment of male infertility.…”
Section: Genetic and Epigenetic Considerations: Risk Of Transmission ...mentioning
confidence: 99%